Intensive Forest Management Planning in Bastar - Mahalaha, S. H. (Indian Forester, 1975)
There must be concerned drive to increase forestry production, to off-set the Crisis created by shortage of these raw-materials as envisaged by National Commission on Agriculture. Baster Forests, which make 3 percent of the country's forest area and 7.19 percent of the growing stock, have largely remained unexploited. Inspite of strategic location, hospitable terrain, availability of natural resources and presence of industrial pre-requisites, these forests have remained unexploited in absence of industrial planning. In order to utilize these forests on anything like the scale possible industrial planning was taken in hand. The total forested area was divide into intensive and non-intensive areas and five industrial wood supply to the consuming centres keeping maximum economics in transportation and production costs. All industrially sought-after species which can profitably be grown in the area were selected for specific areas and intensive forestry was prescribed to mobilise these resources under a phased programme.